POPULATION PARAMETERS OF ENDEAVOUR SHRIMP (Metapenaeus ensis de Haan) IN BINUANGEUN AND ADJACENT WATERS, WEST JAVA - Ali Suman; Prihatiningsih Prihatiningsih; Pratiwi Lestari; Andina Ramadhani Putri Pane (Research Center for Fisheries, 2019)
Study on the population dynamic of endeavour shrimp (Metapenaus ensis) was conducted in Binuangeun waters based on data collected during period of survey, January to November 2016. The purpose of the study was to identify population parameters of the endeavour shrimp. Result showed that the endeavor shrimp growth pattern in Binuangeun waters was negative allometric and sex ratio of males and females was 1.0 : 2.7. The chi square test indicated that comparison of male and female of the endeavour shrimp was significantly different. It mean that there was imbalance in number between males and females. The length at first capture (Lc) of endeavour shrimp was 28.9 mm (carapace length),smaller than the length at first maturity (Lm) at 37.7 mm (carapace length). The growth parameter of endeavour shrimp was 1.33/year with maximum carapace length (Loo) of 51.45 mm. Instantenous total mortality (Z) and natural mortality (M) were 7.74/year and 1.88/year, respectively. While fishing mortality (F) and exploitation rate (E) respectively were 5.86/year and 0.76/year. The exploitation rate of endeavour shrimp in Binuangeun and adjacent waters was high. It was, therefore, recommended that fishing effort of the endeavour shrimp in that waters should be reduced about 52 % in the next year.